2016
DOI: 10.4238/gmr.15038794
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interaction network construction for cancer using a new L1/2-penalized Net-SVM model

Abstract: ABSTRACT.Identifying biomarker genes and characterizing interaction pathways with high-dimensional and low-sample size microarray data is a major challenge in computational biology. In this field, the construction of protein-protein interaction (PPI) networks using disease-related selected genes has garnered much attention. Support vector machines (SVMs) are commonly used to classify patients, and a number of useful tools such as lasso, elastic net, SCAD, or other regularization methods can be combined with SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The superiority of this method over the existing sequence-based methods will make it useful for the study of protein networks. Chai et al (69) built a new Net-SVM model which selected fewer but more relevant genes. This Net-SVM can be used to construct simple and informative PPI networks that are highly relevant to cancer.…”
Section: Cancer Gene/protein Interaction and Networkmentioning
confidence: 99%
“…The superiority of this method over the existing sequence-based methods will make it useful for the study of protein networks. Chai et al (69) built a new Net-SVM model which selected fewer but more relevant genes. This Net-SVM can be used to construct simple and informative PPI networks that are highly relevant to cancer.…”
Section: Cancer Gene/protein Interaction and Networkmentioning
confidence: 99%
“…The smaller number of seedlings produced in plastic bags, together with the greater variation amplitude of height (25.60 cm), may have negatively affected the predictive performance of PDF Logistic 2P, Log-logistic 2P, Gamma 2P, Normal and Log-normal. It is important to emphasize that other statistical approaches, such as the use of artificial intelligence and regularized regressions (Binoti et al, 2013;Castro et al, 2013;Binoti et al, 2014;Kadyrova and Pavlova, 2014;Diamantopoulou et al, 2015;Chai et al, 2016), can be applied in order to improve predictive quality in complex database modeling. The most common regularization methods for machine learning focused on regression problems are the Ridge and Least Absolute Shrinkage and Selection Operator (LASSO) (Chai et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that other statistical approaches, such as the use of artificial intelligence and regularized regressions (Binoti et al, 2013;Castro et al, 2013;Binoti et al, 2014;Kadyrova and Pavlova, 2014;Diamantopoulou et al, 2015;Chai et al, 2016), can be applied in order to improve predictive quality in complex database modeling. The most common regularization methods for machine learning focused on regression problems are the Ridge and Least Absolute Shrinkage and Selection Operator (LASSO) (Chai et al, 2016). Biological network-regularized logistic models are examples that have been extensively used in the genomic area (Zhang et al, 2013;Huang et al, 2015;Chai et al, 2016;Huang et al, 2016;Kang et al, 2017), but its application has not yet been found in Brazilian silviculture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not always having the best accuracy, the overall performance of SVM models regardless of the configuration, are modest at the very least. SVM performed well, even with low sample size and high-dimensional dataset like in Chai et al [25] and Matsumoto et al [24]. Similarly, in Durgesh and Lekha [23], SVM can have different kernel functions for various characteristics of a dataset.…”
Section: Literature Analysismentioning
confidence: 98%